Chemical and microbiological characterization of the zootechnical additive VITAFERT, under small-scale production conditions - Beruvides, A.; Elías, A.; Valiño, Elaine C.; Milián, Grethel; Rondón, Ana J.; Rodríguez, Marlén; Milián, J. (Cuban Journal of Agricultural Science, 2021)
The objective of this research was to chemically and microbiologically characterize the zootechnical additive VITAFERT and evaluate its stability for 90 days. To analyze the results of the chemical and microbiological characterization, descriptive statistics (mean, standard deviation and coefficient of variation) was applied. One-way analysis of variance was used to study stability. INFOSTAT package, version 2012, was also used. The performance of the chemical composition was similar similar in the five studied batches, with mean for dry matter (9.70%), ashes (10.5%), calcium (1.33%), phosphorus (0.65%), crude protein (7.12%) and pH (4.0). The additive showed high counts of lactic acid bacteria, with values between 3.24 x 1012 CFU.mL-1 and 4.95 x 1012 UFC.mL-1 and yeasts between 7.00 x 107 CFU.mL-1 and 9.66 x 107 CFU.mL-1 respectively, as well as a pH of 4.0. The stability study showed that the product maintains a pH of 4.0 up to 90 days. It is concluded that the zootechnical additive VITAFERT has chemical and microbiological characteristics for its application in animal feed. Key words: microbial preparation, stability, lactic acid bacteria, yeasts